How do Soccer Teams Coordinate Consecutive Passes? A Visual Analytics System for Analysing the Complexity of Passing Sequences Using Soccer Flow Motifs. - Comba, João Luiz Dihl; Garcia, Rafael; Malqui, Jose Luis Sotomayor; Alemdar, Hande; Romero, Noemí Maritza Lapa (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
The analysis of passing strategies plays a major role in soccer. Soccer managers use scouting, video footage, and soccer data feed to collect information about tactics and player performance. However, the nature of passing strategies is complex enough to reflect what is happening in the match and makes it hard to understand its dynamics. Furthermore, there exists a growing demand for pattern detection and passing analysis popularized by FC Barcelona's tiki-taka. In this paper, we describe a visual analytics system to analyze the sequence and trajectory of consecutive passing sequences. We describe a two-phase clustering algorithm that extracts typical trajectory clusters in passing sequences, which result in eight predominant clusters. The combined analysis of the sequence and trajectory clusters allow experts to perform multi or single-game analysis in various ways. We show the potential of our approach in case studies using data from the Brazilian and Turkish leagues and report feedback from soccer experts.